Faktor yang Memengaruhi Pasien Rawat Inap Pulang Atas Permintaan Sendiri di Puskesmas Teppo - Nurfaiqa, Nurfaiqa; Usman, Usman; Nurlinda , Nurlinda; Muin, Herlina; Rusman , Ayu Dwi Putri (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2026)
Discharge Against Medical Advice (DAMA) is a phenomenon where inpatients terminate their treatment before being medically declared recovered, which can increase the risk of complications and affect the quality of healthcare services. This study aims to analyze the factors causing inpatients to perform DAMA at Teppo Public Health Center, Pinrang Regency. This research employed a qualitative method with a phenomenological approach, involving eight DAMA patients, one nurse, and the head of the health center as informants, using in-depth interviews and observations for data collection. The data ware analyzed using MAXQDA software through coding and thematic analysis. The results revealed four main factors influencing patients to perform DAMA: patients' subjective perception of feeling better despite medically requiring further treatment, family support encouraging patients to go home due to economic reasons, home comfort, and trust in traditional medicine, psychological factors such as boredom, anxiety, restlessness, discomfort, and feelings of awkwardness during hospitalization, and socio-cultural factors including the belief that traditional medicine is more effective and the cultural preference for home-based recovery. This study recommends the need for patient and family education regarding the risks of DAMA, the enhancement of effective communication, and culturally responsive healthcare services to reduce the DAMA rate at Teppo Public Health Center.